Principles of Agricultural Economics - Barkley, Andrew P., 1962-; Barkley, Paul W. (Routledge, 2020)
"Principles of Agricultural Economics, now in its third edition, continues to showcase the power of economic principles to explain and predict issues and current events in the food, agricultural, and agribusiness sectors. This key text introduces economic principles in a succinct and reader-friendly format, providing students and instructors with a clear, up-to-date, and straightforward approach to learning how a market-based economy functions, and how to use simple economic principles for improved decision making. The field of agricultural economics has expanded to include a wide range of topics and approaches, including macroeconomics, international trade, agribusiness, environmental economics, natural resources, and international development and these are all introduced in this text. For this edition, new and enhanced material on agricultural policies, globalization, welfare analysis, and explanations of the role of government in agriculture and agribusiness is included. Readers will also benefit from an expanded range of case studies and text boxes, including more international cases, which discuss real world examples and issues including global hunger, biofuels, trade wars, agritourism, and climate change. This book is ideal for courses on agricultural economics, microeconomics, rural development and environmental policy. The work is fully supported by a companion website which provides users with extra content to enhance their learning and further their understanding of agricultural economics. Additional materials include flash cards, study guides, PowerPoints, multiple choice questions, essay questions, and an instructor's manual"--